Islam Transnasional vs Islam Moderat: Upaya NU dan MD dalam Menyuarakan Islam Moderat di Panggung Dunia - Asroor, Zaimul (JURNAL AT-TURAS, 2019)
Abstract: Transnational ideologies with a "fierce" face such as HTI, Muslim Brotherhood and Salafi have progressed from year to year, especially after the reformation. This is evidenced by their success infiltrated into the bodies of two large Indonesian Islamic organizations known to be very moderate (NU and MD) in the 2006-2007s. In response to this, the 33rd NU conference and the 47th MD conference in 2015 seemed to be evidence of the seriousness of the two organizations to not only improve themselves after being infiltrated but also to make both of them intensified to introduce Indonesian Islamic patterns to the outside. This paper concludes that the face of moderate Islam in Indonesia will be maintained as long as NU and MD remain steadfast as the "bodyguards" of the Republic of Indonesia. More than that, both of them are determined to utter a new Islamic model typical of Indonesia on the world stage, namely Islam Nusantara Berkemajuan. Therefore, the efforts of the transnational movement whose agenda is to replace the foundation of the Indonesian state into a caliphate will end in vain. Keywords: Moderate Islam, Indonesia's Contributions, NU, MD, Transnational Ideology.